1967
DOI: 10.6028/jres.071a.036
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacities and related thermal data for diethyl phthalate crystal, glass, and liquid to 360 K

Abstract: Experimentally determined heat capacity valu es, precise to within 0.1 percent, and related thermal data are reported for quenched and annealed diethyl phthalate glasses from ]0 oK to the glass transformation te mperature, Tg (around 180 O K) , for the liquid from T" to 360 oK, and for the crystal from 10 oK to the melting temperature (269.9 O K). The mole fraction of liquid·soluble, solid·insoluble impurity in the sample as determined by fractional melting was 0.0012. Co mmon thermodynamic properties calc ula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

1968
1968
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 6 publications
2
32
1
Order By: Relevance
“…By using the calorimetric data from Chang et al, 3 Goldstein 13,14 had shown that entropy S exc of annealed diethyl phthalate glass 3 over the entropy of its crystal phase is 22.25 J / mol K at ͑adiabatic calorimetric͒ T g of 178 K. The 0 K entropy of the annealed glass is 20.17 J / mol K and thus the increase in S exc from 0 K to T g for the annealed glass is 2.1 J / mol K. For a diethyl phthalate glass formed by quenching, 3 the increase in S exc over the 0 K value is 3.64 J / mol K higher than the annealed glass at T near T g of 178 K ͑Table I of Ref. 14͒ and at T = 180.8 K, it is 1.7 J / mol K. The increase in the entropy of the quenched glass over the annealed glass is due to several factors: ͑i͒ the entropy difference from greater anharmonicity of vibrational displacement, ͑ii͒ the difference in the vibrational frequencies of the glass and crystal phases, ͑iii͒ the change in the number of configurational states that involve only the ␤-relaxation motions, and ͑iv͒ the loss in the annealed glass of available configurations from the unfrozen modes of molecular motions that show up as the high-frequency tail of the ␣-relaxation time distribution in the dielectric spectra.…”
Section: B Entropy and ␤ Relaxationmentioning
confidence: 99%
See 3 more Smart Citations
“…By using the calorimetric data from Chang et al, 3 Goldstein 13,14 had shown that entropy S exc of annealed diethyl phthalate glass 3 over the entropy of its crystal phase is 22.25 J / mol K at ͑adiabatic calorimetric͒ T g of 178 K. The 0 K entropy of the annealed glass is 20.17 J / mol K and thus the increase in S exc from 0 K to T g for the annealed glass is 2.1 J / mol K. For a diethyl phthalate glass formed by quenching, 3 the increase in S exc over the 0 K value is 3.64 J / mol K higher than the annealed glass at T near T g of 178 K ͑Table I of Ref. 14͒ and at T = 180.8 K, it is 1.7 J / mol K. The increase in the entropy of the quenched glass over the annealed glass is due to several factors: ͑i͒ the entropy difference from greater anharmonicity of vibrational displacement, ͑ii͒ the difference in the vibrational frequencies of the glass and crystal phases, ͑iii͒ the change in the number of configurational states that involve only the ␤-relaxation motions, and ͑iv͒ the loss in the annealed glass of available configurations from the unfrozen modes of molecular motions that show up as the high-frequency tail of the ␣-relaxation time distribution in the dielectric spectra.…”
Section: B Entropy and ␤ Relaxationmentioning
confidence: 99%
“…5͑A͒, for the quenched glass using the diethyl phthalate entropy data for a "quenched glass" reported by Chang et al 3 The ratio ⌬⑀ ␤ / ͓S exc ͑T͒ − S exc ͑0͔͒ is also plotted against T in Fig. 5͑B͒, where S exc ͑T͒ is the excess entropy at T K and S exc ͑0͒ is the excess entropy at 0 K. Since the available entropy data are at 5 or 10 K temperature intervals, with a 20 K gap in the glass and ultraviscous liquid entropy data over the time-dependent, glass-softening or T g range, the S͑T͒ and S exc ͑T͒ values for the temperature at which ⌬⑀ ␤ was measured were interpolated from Chang's data by a cubicspline method.…”
Section: B Entropy and ␤ Relaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…The measuring procedures and methods of data treatment were discussed in more detail in another paper [24].…”
Section: Calorimetric Techniquementioning
confidence: 99%